2018
DOI: 10.1055/s-0044-100523
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Benzodiazepines and Related Drugs in Patients with Mild Cognitive Deficits and Alzheimer’s Disease

Abstract: The inappropriate use of BZDR conflicts with national and international guidelines. We suggest evaluating indications and treatment duration and improving the knowledge of alternative therapies in healthcare institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Previous studies of BZD plus ADep use have found a high probability of combined use when one of the drugs have already been prescribed, 20,45,46 and with higher rates of prescription. 46,47 Commonly these medications are prescribed without a clear indication based on formal diagnosis, lack of a comprehensive geriatric assessment, and inadequate adherence to updated recommendations for prescription in older adults with dementia.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies of BZD plus ADep use have found a high probability of combined use when one of the drugs have already been prescribed, 20,45,46 and with higher rates of prescription. 46,47 Commonly these medications are prescribed without a clear indication based on formal diagnosis, lack of a comprehensive geriatric assessment, and inadequate adherence to updated recommendations for prescription in older adults with dementia.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies of BZD plus ADep use have found a high probability of combined use when one of the drugs have already been prescribed, 20 , 45 , 46 and with higher rates of prescription 46 47…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We conducted subgroup analyses of BZD abusers (Figure 3). Seven studies included participants with BZD abuse (38,40,41,43,45,47,48) (Table 1). In the BZD abuse subgroup, the abusers received significantly lower MMSE scores compared to the controls (n=7726; SMD: -0.23, 95% CI: -0.44 to -0.03, I² = 86%, p =0.02).…”
Section: Benzodiazepine Abuse and Cognitive Decline In The Eldersmentioning
confidence: 99%